Increase in oxidative stress and mitochondrial impairment in hypothalamus of streptozotocin treated diabetic rat: Antioxidative effect of Withania somnifera - Parihar, P; Shetty, R; Ghafourifar, P; Parihar, M S (Cellular and Molecular Biology, 2016)
Hypothalamus, the primary brain region for glucose sensing, is severely affected by oxidative stress in diabetes mellitus. Oxidative stress in this region of brain may cause severe impairment in neuronal metabolic functions. Mitochondria are prominent targets of oxidative stress and the combination of increased oxidative stress and mitochondrial dysfunctions may further decline hypothalamic neuronal functions. In the present study we examined the oxidative damage response, antioxidative responses and mitochondrial membrane permeability transition in hypothalamus of streptozotocin-treated diabetic rats. Our results show that streptozotocin significantly increases hypothalamic lipid peroxidation, protein carbonyl content while glutathione peroxidase and reduced glutathione were declined. Mitochondrial impairment marked by an increase in mitochondrial membrane permeabilization was seen following streptozotocin treatment in the hypothalamus. The oral administration of Withania somnifera root extract stabilized mitochondrial functions and prevented oxidative damage in the hypothalamus of diabetic rat. These findings suggest an increase in the oxidative stress and decline in antioxidative responses in the hypothalamus of streptozotocin treated diabetic rats. Withania somnifera root extract was found useful in reducing oxidative stress and mitochondrial impairment in hypothalamus of diabetic rat.